A scaffolding for low english proficiency: designing and english for academic purposes course for bachelor of business administration students - Hussain, Z.D. (My University, 2018)
This research is aimed at establishing the necessity for a needs based English for Academic Purposes type of language course for the first year undergraduates following the English medium BBA (Bachelor pf Business Administration) Degree in the Faculty of Finance and Management in a Sri Lankan state university. The research was motivated by the lack of a needs based language course for the 'remedial students' (students who score below 40% in the English Placement Test, who are considered to struggle the most with the English medium instruction) in every batch. The study was guided by ESP/EAP research and concepts such as needs analysis, corpus analysis and curriculum design. These concepts were used to develop a conceptual framework for guiding the steps of this research and to progress towards its objectives keeping within the underlying principles of EAP course design. Research methods used included questionnaire surveys, interviews with students (both first year and senior), the language course designer and subject lecturers and corpus analysis of BBA course content, namely lectures. The results of the study indicate that the first year, especially the first semester is a linguistic transition period in which students with low English proficiency face the challenge of learning academic subject content in a less proficient language English and scoring adequate marks in assessments for academic success. In this scenario, it would not be constructive for such students to be provided with a General English assistance program. An academic English program according to preconceived views of the language assistance providers will also not be adequate as it will lack understanding of the requirements of the students' higher studies environment, students' challenges and needs and thus be unsuccessful in filling the immediate language requirements of the students. An academic program that is closely linked with the content and activities of the BBA degree subjects ...